TOWARD GOVERNMENT WITHOUT CORRUPTION, COLLUSION, AND NEPOTISM WITH GOOD GOVERNMENT GOVERNANCE - Sulistiani, Dwi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Completion of public organizations are expected to lead to the establishment of an open-system organizations more flexible, able to accommodate changes to the organization. Rapidly changes and unpredictable open views and thoughts on the demands of a new paradigm that delivers way to "Good Government Governance" (Good Governance), to the government free of corruption, collusion and nepotism (KKN). In the modern organization rests on the concepts of modern management thinking, among other things: implementing management technology, based on the principles of Democratization, accountability, openness, transparency and law-abiding. The implementation of "Good Government Governance" is a prerequisite for any government to realize the people's aspirations and achieve the goals and ideals of the nation state. In order that required the development and implementation of appropriate systems of accountability, clear and legitimacy, so the government administration and development can take place fruitfully, effecfive, clean and responsible, and free from corruption, collusion and nepotism (KKN). The realization of the implementation of Government Good Governance in governmental organizations is a demand for the implementation of government management and the development of efficient, effective and free of corruption, collusion and nepotism. In this regard the necessary system akutabilitas, transparency, openness and the rule of law and in accordance with the expectations / demands at all levels of the State apparatus.